Usage of diuretics among diabetic-hypertensive patients - Shastry, Rajeshwari; Adhikari, M.R. Prabha; Ullal, Sheetal D.; Kotian, Shashidhar (Asian Journal of Medical Sciences, 2014)
Background: Hypertension is more common in diabetics than in non-diabetic patients. An aggressive approach to the diagnosis and treatment of hypertension in patients with diabetes is required in order to substantially reduce the incidence of both macro-vascular and micro-vascular complications. The role of diuretics in the treatment of hypertension as first line or second line drugs is a provoking debate, hence we studied the usage of diuretics and their effects on BP and glycemic control among diabetic-hypertensive patients. Methods: This cross sectional study was carried out for a period of six months in a tertiary care teaching hospital. Patients’ details such as age, gender, height, weight, comorbid diseases, blood pressure, eGFR along with duration of diabetes and hypertension and drugs prescribed for hypertension were noted. Data were analyzed using descriptive statistics. Results: A total of 336 diabetic-hypertensiveswith a mean age of 64.55±9.51 years were included. Fortyfive patients were on diuretics,two (4.4%) of whom were on diuretic monotherapy, 16 (35.6%) on two drug combinations (Diuretic + ACEI or ARB), 21 (46.7%) on three drug combinations (diuretics + ARB & BBs or diuretic + ACEI & BB or diuretic + ARB &CCB) and six (13.3%) were on four drug combinations (diuretics + ARB, CCB & BB). Among the patients on diuretic combination therapy BP was well controlled in 23 (51%) patients and the glycemic control was comparable to those not on diuretics. Conclusion: In the present study the usage of diuretics was consistent with the guidelines. About 13% of diabetic-hypertensive patients were on diuretic treatment. The control of BP in patients on diuretics was not satisfactory, but there was no worsening of glycemic control compared to other antihypertensive therapy. This shows that low dose thiazides in combination with other antihypertensives can be safe in diabetic-hypertensive patients however their efficacy needs further scrutiny. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10582 Asian Journal of Medical Sciences Vol.6(2) 2015 15-18